Construction of a dust chamber didactic kit and computational fluid dynamics assessment: an active learning practice (Research, Society and Development, 2020)
Laboratory practices for separation of solid-gas mixtures are part of the curriculum of different engineering courses. The objective of this work was the construction and evaluation of a didactic bench kit for particles separation in the gravitational chamber, used industrially for dust collection. The kit was designed and built by students from the Unit Operations Laboratory discipline, which used the Oriented Project, as an active teaching methodology. Thus, this work is relevant because incorporates an active method in the building process of knowledge, it also enables the acquisition of low-cost equipment for teaching laboratories. The geometry of the separation chamber was compact and used a cooler to promote air supply. About 234.5 g of sand was fed at the entrance of the equipment. After collecting the particles throughout the chamber, the samples were sieved, in order to calculate the individual collection efficiency. The cutting diameter of the particles retained in each compartment was calculated by literature correlations and computational fluid dynamics simulations. Through the simulations, the air velocity profile inside the chamber and the trajectory of the particles were obtained. The experimental results showed a global collection efficiency close to 100%, in which about 94% of the particles were collected in the first compartment. The cutting diameter values predicted by correlations and computer simulations were similar and close to those observed experimentally. Thus, this work developed a simple, low-cost and efficient didactic kit for solid-gas separation.